2005
DOI: 10.1016/j.comppsych.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of the Hamilton Depression Rating Scale: is increased efficiency possible? A post hoc comparison of Hamilton Depression Rating Scale, Maier and Bech subscales, Clinical Global Impression, and Symptom Checklist-90 scores

Abstract: Background: The 17-item Hamilton Depression Rating Scale (HDRS) is used as a semi-gold standard in research. In treatment guidelines, the HDRS measurements serve to determine response and remission and guide clinical decision making for nonresponders. However, its use in clinical practice is limited, possibly because the HDRS is time consuming. In addition, the multidimensional HDRS is criticized for not measuring a unidimensional aspect as depression severity. The Maier and the Bech, two 6-item severity subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 44 publications
(92 reference statements)
3
54
0
Order By: Relevance
“…Both Ruhe et al [20] and Kyle et al [21] found that a score <5 on the HAM-D 6 or <8 on the HAM-D 17 was obtained using CGI-S as reference for remission. These remission cut-off scores are important when using remission rates as outcome in treatment studies.…”
Section: Resultsmentioning
confidence: 99%
“…Both Ruhe et al [20] and Kyle et al [21] found that a score <5 on the HAM-D 6 or <8 on the HAM-D 17 was obtained using CGI-S as reference for remission. These remission cut-off scores are important when using remission rates as outcome in treatment studies.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary analyses indicated that, with the CGI-I, clinicians tended to overestimate the actual result of pharmacotherapy compared to patient reports. It may be advisable to use more specific instruments than the CGI, such as a short form of the HAM-D [74], which can be easily administered during pharmacotherapy consultations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, items representing the reversed vegetative symptoms of depression (e.g., hyperphagia, hypersomnia, and weight gain), which recently have been considered to be especially pertinent among patients with bipolar disorder (Thase, 2005) were eliminated because of poor item characteristics. Several items associated with somatic and neurovegatative symptoms (e.g., appetite decrease, hypochondriasis, and weight loss) also performed poorly, which is somewhat inconsistent with the common criticism that the HDRS is overly sensitive to these symptoms (e.g., Bagby et al, 2004;Ruhe et al, 2005). It is possible that the participants in this sample tended to attribute any physiologically-based experiences to their post-acute withdrawal symptoms stemming from recent substance use and/or to medication side effects rather than to depression per se (e.g., Gao and Calabrese, 2005;Maremmani et al, 2006;Perugi et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…Decades of research with the HDRS have resulted in many item modifications, and consequently have led to concerns about the scale's theoretical underpinnings, psychometric properties, and administration procedures. (e.g., Bagby et al, 2004;Ruhe et al, 2005;Santor and Coyne, 2001;Williams, 2001). Despite these concerns, various versions of the HDRS continue to be used in outcome-oriented investigations (e.g., Brown et al, 2006;Chengappa et al, 2000b;Gao and Calabrese, 2005;Nunes and Levin, 2004) that guide the development of pharmacotherapy and psychotherapy.…”
Section: Introductionmentioning
confidence: 99%